Propuesta de un programa de fuerza a través de ejercicios naturales para escolares de 12 años de edad que estudian el séptimo año de la educación básica en la unidad educativa “Medardo Ángel Silva” - Ayovi Baez, Eddy Fabricio (2016)
This research aims to design a program supported by natural physical exercises for strength development in students in the subjects investigated. The central problem is addressed: How will impact a program supported by natural exercises to develop strength in the seventh year students of Basic Education of the Education Unit "Medardo Ángel Silva" Francisco de Orellana Canton ?, the objective They are generally Inductive Method - Deductive, The Analytical Method - Synthetic, Descriptive Method The population had three teachers and 120 students. The techniques and instruments were; surveys, questionnaires, and test. We conclude that the body strength affects muscle growth and physical strength of the practitioners, through natural exercises or exercises with your own body weight, being shown that teachers do not have the necessary knowledge to develop this kind of force in physical education classes, thus affecting the development of their physical abilities related to strength, endurance and strength to speed. Keywords: Strength, body physical education physical abilities,